Improving Students’ Vocabulary By Using Anagram Game - Mariyani, Husna; Saputra, Ajah; Kinanti, Rini (Jurnal Ilmiah Mandala Education (JIME), 2024)
Vocabulary is important especially for ability to speak, listen, write, and read. In teaching and learning process, students less interest and monotonous method, causes students’ low vocabulary. In other words, anagram game can be used to solve the problem. The objective of the research is to find out the difference mean score of the students who are tough through anagram game and students who are tough without anagram game. This research applied quasi-experimental. The sample of the research were the students of 7-5 as experimental class and 7-3 as control class at SMP Negeri 3 Sampit. The data collection was used try-out, pre-test, treatment, and post-test. Based on the data gained, the students’ mean score of pre-test (52.22) in experimental class were lower than the mean score of pre-test (53.00) in control class. Meanwhile, the students’ mean score of post test (67.78) in experimental class higher than the mean score of post-test (59.22) in control class. The value of t-test (5.698) was higher than t-table (1.994). Therefore, Ho was rejected and Ha was accepted. Through a comparative quantitative technique that uses a t-test, the study concluded that there were significant different mean score between students who are tough through anagram game and students who are tough without anagram game.Keyword: Vocabulary; Anagram game; Students’ vocabulary score